Analysis of Long-Term Durability Monitoring Data of High-Piled Wharf with Anode-Ladder Sensors Embedded in Concrete - Liu, Hongbiao; Zhang, Baohua; Liu, Haicheng; Ji, Zifan (Frontiers in Materials, 2021)
The structural durability monitoring (SDM) system for a high-piled wharf in the Tianjin Port of China is devised and deployed with an anode ladder sensor, which provides a means to monitor the state of steel corrosion for the wharf. In this project, the anode-ladder sensors are installed on the reinforced concrete components of the front platforms. After the installation, the monitoring data from the anode-ladder sensor was collected for 40 months. Based on the monitoring data for 40 months, it is proven that the resistance of concrete will be significantly affected by the change in temperature, and the increase in temperature will cause the drop in concrete resistance. Furthermore, the data of the anode-ladder sensor set in the track beam of the front platform shows that the current in anode A1 and A2 relative to the cathode exceeded 15μA during the four-month period, which is abnormal. The main reason is the influence of concrete temperature and humidity. Therefore, the monitoring data for current, voltage, resistance, and temperature should be combined to determine the activation state of the anode, and cannot be determined simply using the current value.